Networked Unionism: Reframing the Labour Movement and Starbucks Workers United’s Hybrid Organising Practices - Gino Canella (tripleC: Communication, Capitalism & Critique, 2023)
Union organising is surging in the United States, especially among younger workers in the service industries. This article examines this uptick in labour organising through a case study of Starbucks Workers United (SBWU). I studied this campaign from March to December 2022 using a variety of online and offline methods: conducting twenty-three in-depth interviews with SBWU organisers; attending strikes, direct actions, and planning meetings; and following these groups on social media. This study addresses two main questions: How are SBWU organisers communicating unionisation with their co-workers and to broader publics? And, how are social media influencing workers’ organising practices? Despite claims that social media are “a great radicaliser”, this study demonstrates how workers were politicised by their material conditions in an industrialising workplace. While media helped organisers amplify their messages and recruit new members, the social relationships among organisers were central to SBWU’s early growth. By detailing how organisers navigated the contradictions within networked media, this study shows how worker-led campaigns like SBWU are reshaping the structure and composition of the US labour movement.